PENGARUH PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI TRIGONOMETRI - Muhammad Kaluwih Pangertian Junaidi; Moch. Lutfianto (Jurnal Pembelajaran Matematika, 2018)
Abstract :The study discusses the effect of applying problem-based learning model (PBL) on students’ learning outcomes at class X TAV I of State Vocational School (SMKN) 3 Surabaya. The objectives of this study are to find out: (1) mathematics learning outcomes at class X TAV I of State Vocational School (SMKN) 3 Surabaya before the application of PBL model 2) learning outcomes of students taught with PBL model, and 3) the effect of applying PBL model on learning outcomes at class X TAV I of State Vocational School (SMKN) 3 Surabaya. This study uses pre-experimental design in the form of one group pretest-posttest design. The population in this study are all students at class X TAV I of State Vocational School (SMKN) 3 Surabaya, consisting of 33 students. The sampling technique is a saturated sample technique. The instruments in this study are Pre-test and Post-test results. Data analysis technique uses descriptive statistics. The results show that the average value of the participants before being taught with PBL model is 51.94 and the average value after being taught with PBL model up to 52.88. The result of descriptive statistical analysis is r count 0.753771922 > r table 0.632. Meanwhile, the results of statistical calculation analysis is 0.05 (0.632 <0.753771922) with credibility level up to 95%. It means that there is an effect of PBL model on students’ learning outcomes because H0is rejected and Ha is accepted.Keywords:Problem based learning (PBL) model, Mathematics Learning Outcomes.